Foundations for a green economy: how institutions shape green skills - Marius R. Busemeyer; Martin B. Carstensen; Achim Kemmerling; Jale Tosun (npj Climate Action)
Abstract Policymakers, companies, trade unions, and civil society actors increasingly recognize the urgent need to facilitate the transition to a low-carbon economy. This Perspective highlights the critical role of “green skills” in this transition. Our article identifies avenues for future research, grounded in the institutional foundations of skill formation processes. We emphasize the global nature of this challenge and the diverse institutional contexts in which green skills must be developed.